Evidence of Brain Alterations in Noncerebral Falciparum Malaria. (15th December 2021) - Mohanty, Sanjib; Sahu, Praveen K; Pattnaik, Rajyabardhan; Majhi, Megharay; Maharana, Sameer; Bage, Jabamani; Mohanty, Akshaya; Mohanty, Anita; Bendszus, Martin; Patterson, Catriona; Gupta, Himanshu; Dondorp, Arjen M; et al.
Abstract: Background: Cerebral malaria in adults is associated with brain hypoxic changes on magnetic resonance (MR) images and has a high fatality rate. Findings of neuroimaging studies suggest that brain involvement also occurs in patients with uncomplicated malaria (UM) or severe noncerebral malaria (SNCM) without coma, but such features were never rigorously characterized. Methods: Twenty patients with UM and 21 with SNCM underwent MR imaging on admission and 44–72 hours later, as well as plasma analysis. Apparent diffusion coefficient (ADC) maps were generated, with values from 5 healthy individuals serving as controls. Results: Patients with SNCM had a wide spectrum of cerebral ADC values, including both decreased and increased values compared with controls. Patients with low ADC values, indicating cytotoxic edema, showed hypoxic patterns similar to cerebral malaria despite the absence of deep coma. Conversely, high ADC values, indicative of mild vasogenic edema, were observed in both patients with SNCM and patients with UM. Brain involvement was confirmed by elevated circulating levels of S100B. Creatinine was negatively correlated with ADC in SNCM, suggesting an association between acute kidney injury and cytotoxic brain changes. Conclusions: Brain involvement is common in adults with SNCM and a subgroup of hospitalized patients with UM, which warrants closer neurological follow-up. Increased creatinine in SNCM may render the brain more susceptible to cytotoxic edema. Abstract : Quantitative brain magnetic resonance imaging analyses of cerebral tissue water diffusion showed brain changes in adults with severe noncerebral malaria and uncomplicated malaria, suggesting that Plasmodium falciparum infection often affects this organ, despite the absence of coma.